GAMBARAN MOTIVASI DAN TINDAKAN KEPERAWATAN DALAM PEMENUHAN KEBUTUHAN SPIRITUAL PASIEN DI RUANG ICU PKU MUHAMMADIYAH GOMBONG - Ristianingsih, Dwi; Septiwi, Cahyu; Yuniar, Isma (Jurnal Ilmiah Kesehatan Keperawatan, 2014)
Nursing holistic includes biology, psychology, sociology and spiritual. The role of the nurse in meeting the spiritual needs of patients is a part of the role and function of nurses in the nursing care. Motivation of nurses is the main key of nursing care success. This study aims to prove the description motivation and nursing actions in spiritual care in the Intensive Care Unit PKU Muhammadiyah Gombong Hospital. This is a non-experimental descriptive study using cross sectional approach. The populations are 13 respondents. The samples are 12 respondents taken by total sampling. The result shows that 58.3% respondents have mediocre category of motivation. 58.3% respondents have mediocre categories in the spiritual nursing actions. Â  Keywords: motivation of nurses, nursing actions, spiritual